Digital measurement of tooth wear in sleep bruxism patients wearing occlusal splints - Irene Laksamikeeratikul; Supawadee Jariyasakulroj; Thiprawee Chattrattrai; Sunee Pongrojpaw (BMC Oral Health)
Abstract Background Sleep bruxism is a common parafunctional activity that can lead to progressive tooth wear and long-term restorative consequences. Although occlusal splints are widely used to prevent tooth surface loss, the extent of wear in splint-wearing patients remains insufficiently explored. This study aimed to evaluate volumetric tooth wear in canines and first molars among sleep bruxism patients treated with occlusal splints using digital intraoral scanning. Methods A prospective cohort of 16 patients (mean age 27.9 ± 4.5 years) diagnosed with sleep bruxism and wearing polymethyl methacrylate (PMMA) upper occlusal splints was followed for 18 months. Intraoral scans were performed at baseline and follow-up using the TRIOS 4® scanner. Volumetric wear was assessed on the masticatory surfaces of upper and lower canines and first molars using best-fit superimposition and STL analysis software. Statistical comparisons of model volume between upper and lower teeth and between timepoints were performed using the Wilcoxon signed-rank test with a significant level of 0.05. Results All tooth groups showed statistically significant volumetric tooth reduction over 18 months (p < 0.001). However, no significant differences in wear were observed between the upper and lower arches for either canines (p = 0.940) or first molars (p = 0.207). Grinding-type bruxism was more prevalent than clenching-type in the cohort (11 grinding-type and 5 clenching-type patients). Conclusions While PMMA splints may help reduce tooth wear during sleep-related bruxism, measurable tooth wear still occurred. Therefore, effective management of sleep bruxism requires combining splint therapy with comprehensive strategies, such as behavioral and dietary counseling, and regular monitoring.